2018
DOI: 10.1093/ndt/gfy048
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response to fluid removal during hemodialysis: categorization of causes of intradialytic hypotension

Abstract: The hemodynamic profiles clearly define specific hemodynamic mechanisms of cardiac power reduction and/or vasodilatation as underlying intradialytic hypotensive episodes. A reduction in cardiac power (reduction of both blood pressure and cardiac output) could be the result of preload reduction due to a high ultrafiltration rate with not enough refilling or low target weight. A reduction in peripheral resistance (reduction in blood pressure and increase in cardiac output) could be the result of relative vasodil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…Three of the 5 studies that used IDH definitions with multiple cutoff values reported an IDH prevalence of 4.5% [30] and 5.4% [19], and 23.3% [27] at session level but did not specify the used definitions (online suppl. File 3).…”
Section: Prevalence Of Idh On Session Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the 5 studies that used IDH definitions with multiple cutoff values reported an IDH prevalence of 4.5% [30] and 5.4% [19], and 23.3% [27] at session level but did not specify the used definitions (online suppl. File 3).…”
Section: Prevalence Of Idh On Session Levelmentioning
confidence: 99%
“…Of the 5 studies that used definitions with multiple cutoff values, 2 reported a proportion of patients with frequent IDH was 57% [38] and 26% [27]. In the 5 studies that did not provide detailed information on the IDH definition, the proportion of patients with frequent IDH ranged between 4.8% [26] and 76.4% [6], (online suppl.…”
Section: Proportion Of Patients With Frequent Idhmentioning
confidence: 99%
“…Subjects who are prone to IDH have reductions in overall cardiac contractility, leading to reductions in cardiac power output (11). Cardiac power may be reduced due to reductions in preload from high ultrafiltration rates (15). In the present study, CPI during the EX session was higher compared to the CON session.…”
Section: Discussionmentioning
confidence: 44%
“…The NICaS device measures CPI (W/m 2 ) (15). CPI may decrease in subjects undergoing hemodialysis treatment due to less contractile force production from impaired coronary blood flow (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation